Cardiorenal syndrome: Multi‐organ dysfunction involving the heart, kidney and vasculature. (13th May 2020) - Savira, Feby; Magaye, Ruth; Liew, Danny; Reid, Christopher; Kelly, Darren J.; Kompa, Andrew R.; Sangaralingham, S. Jeson; Burnett, John C.; Kaye, David; Wang, Bing H.
Abstract : Cardiorenal syndrome (CRS) is a multi‐organ disease, encompassing heart, kidney and vascular system dysfunction. CRS is a worldwide problem, with high morbidity, mortality, and inflicts a significant burden on the health care system. The pathophysiology is complex, involving interactions between neurohormones, inflammatory processes, oxidative stress and metabolic derangements. Therapies remain inadequate, mainly comprising symptomatic care with minimal prospect of full recovery. Challenges include limiting the contradictory effects of multi‐organ targeted drug prescriptions and continuous monitoring of volume overload. Novel strategies such as multi‐organ transplantation and innovative dialysis modalities have been considered but lack evidence in the CRS context. The adjunct use of pharmaceuticals targeting alternative pathways showing positive results in preclinical models also warrants further validation in the clinic. In recent years, studies have identified the involvement of gut dysbiosis, uraemic toxin accumulation, sphingolipid imbalance and other unconventional contributors, which has encouraged a shift in the paradigm of CRS therapy.